Initial Awareness as Perceived by a Group of Senior Students Majoring in High School Teaching in regards to their Own Teaching Process Focused on Assessment Activities - Gerardo Ignacio Sánchez-Sánchez; Ximena Elizabeth Jara-Amigo (Revista Electrónica Educare)
Developed in a regional campus of a university located 200 miles south of Santiago de Chile, the research showed the initial awareness of 50 senior students majoring in three High School Teaching Training Programs: Spanish Language; History; and Math, in regards to their own teaching process The qualitative approach used in this research is supported by the grounded theory. The critical incident technique was used to obtain the information about the individuals mentioned above, after their first period as in-practice High School teachers. Results show that the assessment teaching functions are mostly mentioned as essential to improve their teaching activities focused on the learning process of high school students. However, Teacher Training Programs should also emphasize real challenges and the abilities that a teacher must successfully develop during the process, instead of mainly focusing on measurement instruments and theoretical outlines